Association between contemporary hormonal contraception and ovarian cancer in women of reproductive age in Denmark: prospective, nationwide cohort study. (26th September 2018) - Iversen, Lisa; Fielding, Shona; Lidegaard, Øjvind; Mørch, Lina S; Skovlund, Charlotte W; Hannaford, Philip C
Abstract: Objectives: To investigate the association between contemporary combined hormonal contraceptives (including progestogen types in combined preparations and all progestogen-only products) and overall and specific types of ovarian cancer. Design: Prospective, nationwide cohort study. Setting: Denmark, 1995-2014. Participants: All women aged 15-49 years during 1995-2014 were eligible. Women were excluded if they immigrated after 1995, had cancer (except non-melanoma skin cancer), had venous thrombosis, or were treated for infertility before entry (final study population included 1 879 227 women). Women were categorised as never users (no record of being dispensed hormonal contraception), current or recent users (≤1 year after stopping use), or former users (>1 year after stopping use) of different hormonal contraceptives. Main outcome measures: Poisson regression was used to calculate relative risk of ovarian cancer among users of any contemporary combined hormonal contraceptives and by progestogen type in combined preparations and all progestogen-only products, including non-oral preparations. Separate analyses examined women followed up to their first contraception type switch and those with full contraceptive histories. Duration, time since last use, and tumour histology were examined and the population prevented fraction were calculated. Results: During 21.4 million person years, 1249 incident ovarian cancers occurred. Among ever users of hormonal contraception, 478 ovarian cancers were recorded over 13 344 531 person years. Never users had 771 ovarian cancers during 8 150 250 person years. Compared with never users, reduced risks of ovarian cancer occurred with current or recent use and former use of any hormonal contraception (relative risk 0.58 (95% confidence interval 0.49 to 0.68) and 0.77 (0.66 to 0.91), respectively). Relative risks among current or recent users decreased with increasing duration (from 0.82 (0.59 to 1.12) with ≤1 year use to 0.26 (0.16 to 0.43) with >10 years' use; P<0.001 for trend). Similar results were achieved among women followed up to their first switch in contraceptive type. Little evidence of major differences in risk estimates by tumour type or progestogen content of combined oral contraceptives was seen. Use of progestogen-only products were not associated with ovarian cancer risk. Among ever users of hormonal contraception, the reduction in the age standardised absolute rate of ovarian cancer was 3.2 per 100 000 person years. Based on the relative risk for the never use versus ever use categories of hormonal contraception (0.66), the population prevented fraction was estimated to be 21%—that is, use of hormonal contraception prevented 21% of ovarian cancers in the study population. Conclusions: Use of contemporary combined hormonal contraceptives is associated with a reduction in ovarian cancer risk in women of reproductive age—an effect related to duration of use, which diminishes after stopping use. These data suggest no protective effect from progestogen-only products.